Urinary Tract Infection - The Result of the Strength of the Pathogen, or the Weakness of the Host 2018
DOI: 10.5772/intechopen.72430
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections in Renal Transplant Recipients

Abstract: Renal transplantation (RTx) is the treatment-of-choice for a significant number of patients with end-stage renal disease. Despite recent accomplishments, both surgical and medical complications still exist. Urinary tract infection (UTI) is the most common infectious complication after RTx, while asymptomatic bacteriuria is the most common manifestation of bacteriuria. UTI can impair graft function, potentially reducing graft and patient survival.The aetiology changes with time after RTx. The epidemiology of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The higher incidence of UTI observed in females (58%) compared to males (42%) is consistent with global trends and can be explained by anatomical and physiological factors that predispose women to UTIs, such as a shorter urethra and its proximity to the anus. [22] This nding aligns with numerous studies that have consistently reported a higher risk of UTIs in females across various populations.…”
Section: Discussionsupporting
confidence: 88%
“…The higher incidence of UTI observed in females (58%) compared to males (42%) is consistent with global trends and can be explained by anatomical and physiological factors that predispose women to UTIs, such as a shorter urethra and its proximity to the anus. [22] This nding aligns with numerous studies that have consistently reported a higher risk of UTIs in females across various populations.…”
Section: Discussionsupporting
confidence: 88%
“…In the RESITRA cohort the distribution of UTI during the first three months of the transplant were 82% cystitis and 18% APN [1]. While other studies, the distribution of UTI during the first 6 years after transplantation were: AB 18.4 and 38%, cystitis 7.6 and 25%, APN 12.5 and 22%, and urosepsis 4% [16,17].…”
Section: Review Articlementioning
confidence: 71%
“…Although there is no absolute observational statement, Golebiewska [16] suggests that UTI can be a cause and consequence of acute rejection. His group observed that UTI happening just after the transplant deteriorated the renal function from the early time, explaining it by a scarring process which lead to unrecuperate the basal creatinine, even though this event did not increase the mortality or the rejection.…”
Section: Review Articlementioning
confidence: 99%
See 2 more Smart Citations